Imaginária retabular colonial em São Paulo: estudos iconográficos - Passos, Maria José Spiteri Tavolaro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
everal artistic languages flourished during the Brazilian colonial period and, among them, numerous samples reminiscent from the traditional sculpting technique applied to the construction of religious images may still be found. Designed for religious or civil spaces, the tridimensional production of sculpture character ranges from the elaboration of ornamental elements to the making of figures of saints (sacred images). Imbued by the rigid principles of the Counter-Reformation, the cult of saints became a powerful instrument of evangelization and catechesis, being disseminated after the 16th century by the activity of the religious orders in Brazil, which widely favored the popularization of the cult images, initially imported from Portugal and later produced in the very colony as well. These images would occupy the thrones in the niches of altarpieces in churches, chapels, household oratories and, on festivities, would gain the streets in processions. It is important to emphasize how fundamental the contribution of the third orders and brotherhoods were to disseminate and consolidate this vast work developed among local communities. From the 19th century on, changes in Brazilian politics, economy and society favored the entrance of new esthetic standards coming from Europe. This fact lead many churches to opt for reforms, including the replacement of pieces in clay or wood for new ones executed in series, which resulted in the loss of several ancient originals. However, even though frequently disregarded by studies, a significant number of works executed according to the traditional techniques is still maintained in catholic temples across the state of São Paulo, both in the capital and the interior or the coast. Through the inventory of a representative part of this collection, this work studied the religious imagery reminiscent of the colonial period, with emphasis in the erudite production for ...

Diversas linguagens artísticas se desenvolveram no período colonial brasileiro e, entre elas, ainda se encontram preservados numerosos exemplares remanescentes da tradicional técnica da escultura aplicada à construção de imagens religiosas. Destinadas a espaços religiosos ou civis, a produção tridimensional de caráter escultórico abrangeu desde a elaboração de elementos ornamentais até a realização de figuras de santos (imagens sacras). Imbuído dos rígidos princípios da Contrarreforma, o culto aos santos se tornou um poderoso instrumento evangelizador e catequético, sendo difundido a partir do século XVI, pela atividade das ordens religiosas no Brasil, que em muito favoreceram a popularização das imagens inicialmente importadas de Portugal e posteriormente, também produzidas na própria colônia. Essas imagens ocupariam os tronos nos nichos dos retábulos de altares das igrejas, capelas, oratórios domésticos e, nos dias de festa, sairiam às ruas em procissões. É importante destacar quão fundamental foi a contribuição das ordens terceiras e irmandades para a difusão e consolidação deste vasto trabalho, desenvolvido entre as comunidades locais. A partir do século XIX, mudanças de ordem política, econômica e social, favoreceram a entrada de novos padrões estéticos vindos da Europa, fazendo com que muitas igrejas optassem por realizar reformas, chegando a substituir os exemplares executados em barro ou em madeira, por novas peças, agora executadas em série, conduzindo à perda de muitos dos antigos originais. No entanto, embora pouco estudado, um significativo número de obras executadas segundo as técnicas tradicionais, ainda permanece guardado em templos católicos do Estado de São Paulo, seja na capital, no interior, ou no litoral. O presente trabalho, por meio do levantamento de uma representativa parte desse acervo, estuda a imaginária religiosa remanescente do período colonial...
Keywords: Arte sacra; Escultura; Santos (Arte); Igreja Catolica e arte; Brasil - História - Período colonial, 1500-1822; São Paulo (Estado) - História; Santos (Art)